The Dynamics of Islamic Thought and Practice in Indonesia: History, Transformation, and Relevance in Islamic Education - Rahma, Cut Dewi; Mulia, Muji (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This research aims to describe and analyze the dynamics of Islamic thought and civilization in Indonesia from the perspective of history and ideological transformation, as well as evaluate its relevance and application in Islamic education today. The problems studied include how the intellectual journey of Islam in Indonesia developed from the early days of Islam to the contemporary era, changes in the paradigm of thought from traditionalism to modernism and neo-modernism, and how this thinking can be the basis for the development of adaptive, inclusive and progressive Islamic education. The focus of the research is directed at the ideological transformation of Islamic thought and its relevance in the context of modern Islamic education that is able to shape character and national insight according to the dynamics of today's society. The method used is library research with a historical and intellectual approach, involving the collection, verification, interpretation, and historiography of literary sources such as books, scientific articles, and related documents. The results show that Islamic thought in Indonesia has experienced a dynamic and plural development, ranging from traditional influences that are accommodating to local culture, to the emergence of modern and neo-modern thought that emphasizes rationality, pluralism, and democracy. This transformation has implications for Islamic education, which is now increasingly integrating Islamic values with the needs of the times, forming people with character and insight, and strengthening an inclusive and adaptive national education system.